Increased Serum EphA2 is Associated with Disease Severity in Pediatric Patients with Asthma - Ma S; Qu W (Journal of Asthma and Allergy)
Suli Ma, Weiguang Qu Department of Pediatrics, Pudong New Area People’s Hospital, Shanghai, 201299, People’s Republic of ChinaCorrespondence: Weiguang Qu, Department of Pediatrics, Pudong New Area People’s Hospital, 490 Chuanhuan South Road, Chuansha Town, Pudong New Area, Shanghai, 201299, People’s Republic of China, Tel +86-15000586588, Email 15000586588@163.comBackground: Asthma is the most prevalent chronic inflammatory airway disease in children, with increasing incidence and prevalence. Ephrin type-A receptor 2 (EphA2) belongs to the Ephrin (Eph) family. It is predominantly found in bronchial epithelial cells and may play a potential role in mediating airway inflammation in asthma. However, this study aimed to evaluate the association between a novel biomarker, EphA2, in two distinct pediatric asthma populations stratified by disease severity.Materials and Methods: Serum levels of interleukins (IL-1β, IL-4, IL-6, IL-8, IL-13), tumor necrosis factor-α (TNF-α), transforming growth factor-β 1 (TGF-β 1), matrix metalloproteinase (MMP-2 and MMP-9), and EphA2 were measured by ELISA in all participants. In addition, blood eosinophil counts, Total IgE levels and exhaled nitric oxide (FeNO) levels were evaluated.Results: Serum EphA2 levels in patients with asthma (n=195) were significantly higher than those in healthy controls (n=120), and the levels were notably elevated in patients with severe asthma (n=82) than in those with mild-moderate asthma (n=113). Receiver Operating Characteristic (ROC) curve analysis revealed that the ideal threshold for serum EphA2 was 324.76 pg/mL. This cutoff point demonstrated a sensitivity of 88.7% and a specificity of 92.5%, yielding an Area Under the Curve (AUC) of 0.959. Further correlative analysis indicated that serum EphA2 level was negatively correlated with forced expiratory volume in 1 second (FEV1) (r=− 0.376, P< 0.001), the ratio of FEV1 to forced vital capacity (FVC) (r=− 0.476, P< 0.001), and peak expiratory flow (PEF) (r=− 0.699, P< 0.001). Furthermore, we observed that serum EphA2 positively correlated with Eosinophil count (r=0.227, P=0.001), Total IgE (r=0.715, P< 0.001), FeNO (r=0.560, P< 0.001), IL-1β (r=0.423, P< 0.001), IL-4 (r=0.314, P< 0.001), IL-6 (r=0.625, P< 0.001), IL-8 (r=0.628, P< 0.001), IL-13 (r=0.569, P< 0.001), TNF-α (r=0.562, P< 0.001), TGF-β 1 (r=0.535, P< 0.001), MMP-2 (r=0.273, P< 0.001), and MMP-9 (r=0.266, P< 0.001) in all asthma patients.Conclusion: Our research suggests that EphA2 might be a valuable marker for assessing the risk of exacerbation, inflammation of the airways, and airway remodelling in asthma patients.Keywords: asthma, chronic airway disease, mild-moderate asthma, severe asthma, EphA2